Healthy status and energy balance in pediatrics - Battistini, Nino C.; Poli, Marco; Malavolti, Marcella; Dugoni, Manfredo; Pietrobelli, Angelo (Acta Biomedica Atenei Parmensis, 2006)
During growth, the human body increases in size and changes proportion of various components due to hormones mediators. Nutritional status is the result of introduction, absorption and utilization of the nutrients and it has a new definition in the relationship between nutritional status and healthy status. In this view energy balance, body function and body composition are three entities correlated each other. This mini-review article examines issues and techniques specifically related to a pediatric population in the field of body composition and energy expenditure. It is broadly divided into two sections. The first section discusses body composition measurements underlying principles, advantages, disadvantages and consensus.The second section reviews energy expenditure and physical activity measurement techniques. In conclusion general clinical suggestions are offered regarding pediatric body composition, healthy status and energy balance.